Preoxygenation strategies before intubation in patients with acute hypoxic respiratory failure: a network meta-analysis - Na Ye; Na Ye; Chen Wei; Jiaxiang Deng; Yingying Wang; Hongwen Xie (Frontiers in Medicine)
BackgroundPatients with acute hypoxic respiratory failure (AHRF) face life-threatening complications during tracheal intubation. Preoxygenation can enhance oxygen reserves and mitigate hypoxemia risk, but the optimal strategy remains unclear. This study aimed to identify the best preoxygenation strategy for these patients.MethodsWe conducted a network meta-analysis of studies published up to July 2024, evaluating conventional oxygen therapy (COT), high-flow nasal cannula (HFNC), non-invasive ventilation (NIV), and their combinations prior to intubation. Data were extracted and analyzed using pairwise and network meta-analysis within a Bayesian framework. Model selection was based on the deviance information criterion (DIC).ResultsA total of 11 randomized controlled trials involving 2,874 patients were included. NIV preoxygenation significantly reduced the likelihood of SpO2 <80% during intubation compared to COT (RR 0.28, 95% CI 0.070–0.71). No significant differences were found in lowest SpO2, complications, ICU length of stay, or mortality across preoxygenation strategies. HFNC was the most effective for reducing complications, while HFNC combined with COT or NIV showed similar effects on the lowest SpO2 during intubation.ConclusionPreoxygenation with HFNC appears to be the safest and most effective approach prior to intubation in patients with AHRF compared to other strategies.Systematic review registrationPROSPERO (CRD42024565053).